A review of invasive intracranial pressure monitoring following surgery for hypertensive cerebral hemorrhage - Chen, Fu; Zhang, Shukui; Li, Bingzhen; Zhang, Jin; Ran, Maoxin; Qi, Bin (Frontiers in Neurology, 2023)
Hypertensive cerebral hemorrhage, the most common prevalent of spontaneous cerebral hemorrhage, poses a significant threat to patient mortality and morbidity, while therapeutic options remain limited, making the disease a burden not only for patients’ families but also a major challenge for national healthcare systems. The elevation of intracranial pressure subsequent to hypertensive cerebral hemorrhage is a critical contributor to mortality. However, it often manifests before the onset of clinical symptoms, which are typically atypical, leading to delayed treatment and irreversible consequences for the patient. Hence, early detection of intracranial pressure variations can aid in timely, efficient, and precise treatment, reducing patient mortality. Invasive intracranial pressure monitoring enables real-time, accurate monitoring of intracranial pressure changes, providing clinicians with therapeutic guidance and overcoming the limitations of empirical treatment. This article aims to review the use of invasive intracranial pressure monitoring in postoperative hypertensive cerebral hemorrhage and hopes to contribute to clinical and scientific research.